Bi-allelic loss of function variants of TBX6 causes a spectrum of malformation of spine and rib including congenital scoliosis and spondylocostal dysostosis. Issue 9 (22nd April 2019) - Otomo, Nao; Takeda, Kazuki; Kawai, Shunsuke; Kou, Ikuyo; Guo, Long; Osawa, Mitsujiro; Alev, Cantas; Kawakami, Noriaki; Miyake, Noriko; Matsumoto, Naomichi; Yasuhiko, Yukuto; Kotani, Toshiaki; et al.
Abstract : Background: Congenital scoliosis (CS) is a common vertebral malformation. Spondylocostal dysostosis (SCD) is a rare skeletal dysplasia characterised by multiple vertebral malformations and rib anomalies. In a previous study, a compound heterozygosity for a null mutation and a risk haplotype composed by three single-nucleotide polymorphisms in TBX6 have been reported as a disease-causing model of CS. Another study identified bi-allelic missense variants in a SCD patient. The purpose of our study is to identify TBX6 variants in CS and SCD and examine their pathogenicity. Methods: We recruited 200 patients with CS or SCD and investigated TBX6 variants. We evaluated the pathogenicity of the variants by in silico prediction and in vitro experiments. Results: We identified five 16p11.2 deletions, one splice-site variant and five missense variants in 10 patients. In vitro functional assays for missense variants identified in the previous and present studies demonstrated that most of the variants caused abnormal localisation of TBX6 proteins. We confirmed mislocalisation of TBX6 proteins in presomitic mesoderm cells induced from SCD patient-derived iPS cells. In induced cells, we found decreased mRNA expressions of TBX6 and its downstream genes were involved in somite formation. All CS patients with missense variants had the risk haplotype in the opposite allele, while a SCD patient with bi-allelic missense variants did not have the haplotype. Conclusions: Our study suggests that bi-allelic loss of function variants of TBX6 cause a spectrum of phenotypes including CS and SCD, depending on the severity of the loss of TBX6 function.